Analysis of Public Trust Factors in Zakat Distribution Institutions (Case Study at Lazismu North Labuhanbatu) - Harahap, Adly Zidan; Irawan, Deni (Al Mashaadir : Jurnal Ilmu Syariah, 2024)
As a religion that encompasses various aspects of life, Islam not only touches on the personal dimensions of worship but also on social and economic domains. Zakat represents one of the pillars of Islam with a social character. Every Muslim is obligated to pay zakat on certain assets that are eligible for zakat when these assets reach a specific threshold (nishab) and time period (haul). In Indonesia, there are many legally recognized zakat management organizations that distribute zakat from the community, one of which is the Lembaga Amil Zakat Infaq dan Sadaqah Muhammadiyah (LAZISMU), which is spread throughout Indonesia. This research employs a qualitative approach using observation and in-depth interviews with administrators and local communities from various professions. The study aims to analyze the factors that influence public trust in LAZISMU in Labuhanbatu Utara, North Sumatra. The results show that there are at least five factors that drive public trust in LAZISMU Labuhanbatu Utara, namely: (1) Data transparency, (2) The prominent reputation of the organization, (3) Ease of paying zakat through LAZISMU, (4) The friendliness of the zakat officers, and (5) Various social contributions of the organization to the community. The implications of this study emphasize the importance of data transparency, the development of technology-based services, zakat officer training, and relevant social programs as strategies to build and maintain public trust. These measures can be implemented by LAZISMU and other zakat institutions to enhance effectiveness and gaining more public trust.